2002
DOI: 10.1128/iai.70.5.2361-2367.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival Fibroblasts Rescue Butyric Acid-Induced T-Cell Apoptosis

Abstract: We previously demonstrated that butyric acid, an extracellular metabolite from periodontopathic bacteria, induces cytotoxicity and apoptosis in murine thymocytes, splenic T cells, and human Jurkat T cells. In this study, we used a cell-to-cell interaction system to examine the contribution of gingival fibroblasts to the regulation of T-cell death induced by butyric acid. Butyric acid slightly suppressed fibroblast viability in a concentration-dependent fashion. However, DNA fragmentation assays indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
20
1
1
Order By: Relevance
“…We previously demonstrated that short-chain fatty acids (SCFAs), an extracellular metabolites from periodontopathic bacteria, greatly inhibit proliferation and cytokine production of T and B cells (4). Among SCFAs, butyric acid particularly induces apoptosis in mouse and human T cells (5), B-cells (6), monocytes and macrophages (7), whereas, oral epithelial cells and healthy gingival fibroblasts (8) are resistant to butyric acid-induced apoptosis. Interestingly, inflamed gingival fibroblasts from adults with periodontitis are highly susceptible to butyric acid-induced apoptosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that short-chain fatty acids (SCFAs), an extracellular metabolites from periodontopathic bacteria, greatly inhibit proliferation and cytokine production of T and B cells (4). Among SCFAs, butyric acid particularly induces apoptosis in mouse and human T cells (5), B-cells (6), monocytes and macrophages (7), whereas, oral epithelial cells and healthy gingival fibroblasts (8) are resistant to butyric acid-induced apoptosis. Interestingly, inflamed gingival fibroblasts from adults with periodontitis are highly susceptible to butyric acid-induced apoptosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Butyric acid treatment primarily resulted in increased expression of proapoptotic genes such as Bax, Bad, Bak, and caspase-3, -6, -7, -8, and -9, whereas the expression of antiapoptotic mediators such as Bcl-2 and glutathione was decreased (Table 1). Furthermore, among the MAPKs, the repression profile of butyric acid-treated Jurkat cells was confirmed by means of cDNA array (6).…”
Section: Microarray Analysis Of Jurkat Cellsmentioning
confidence: 80%
“…A sustained phosphorylation was down-regulated after 6 h following treatment with butyric acid. Thus, butyric acid activates the JNK and p38 pathways and at the same time downregulates ERK in Jurkat cells (6).…”
Section: Effect Of Mitochondoria Ceramide and Map Kinase In Butyricmentioning
confidence: 97%
See 1 more Smart Citation
“…We have reported that human gingival fibroblasts rescue butyric acidinduced T-cell apoptosis via proinflammatory cytokines such as interleukin (IL) -6 and IL-11, which are produced by fibroblasts stimulated with butyric acid [30]. The number of Jurkat T-cells adherent to HGFs was significantly increased following the addition of butyric acid.…”
Section: Importance Of Cell-cell Communication In Inhibiting T-cell Amentioning
confidence: 98%